The Relationship Among Four Pillars of Diabetes Mellitus Management with Blood Glucose Levels and Nutritional Status in Middle-Aged Diabetic Adults - Kanthi Permaningtyas Tritisari; Ayuningtyas Dian Ariestiningsih; Dian Handayani; Inggita Kusumastuty (Research Journal of Life Science, 2018)
Controlling the blood sugar level of DM patients is an approach to suppress morbidity and mortality. This study aims to know the relationship of four pillars of DM management with blood glucose levels and nutritional status in patients with type 2 DM in East Java. This study is a cross-sectional study with a sample of middle-aged type 2 DM outpatients in 4 cities in East Java, Indonesia. Four pillars of management include education profile, food planning, physical exercise, and drug adherence. The statistical analysis used was Partial Least Square. The results of the study show that four pillars were not associated with fasting blood glucose (FBG) level and 2-hour PPG in the total number of respondents (p>0.005). Interestingly, dietary intake links to 2-Hour PPG in 40-50 years age group (p=0.000) and was associated with body mass index in the total number of respondents (p=0.000). Furthermore, education profile and medication also related to FBG in 40-50 years age group (p=0.000, p=0,003). In conclusion, the success of the four pillars in controlling DM is affected by age.  In 40-50 years age group, there is an influence of education profile and drug adherence on the level of FBG.